2001
DOI: 10.1074/jbc.m007252200
|View full text |Cite
|
Sign up to set email alerts
|

MgcRacGAP Is Involved in Cytokinesis through Associating with Mitotic Spindle and Midbody

Abstract: We have recently cloned a cDNA for a full-length form of MgcRacGAP. Here we show using anti-MgcRacGAP antibodies that, unlike other known GAPs for Rho family, MgcRacGAP localized to the nucleus in interphase, accumulated to the mitotic spindle in metaphase, and was condensed in the midbody during cytokinesis. Overexpression of an N-terminal deletion mutant resulted in the production of multinucleated cells in HeLa cells. This mutant lost the ability to localize in the mitotic spindle and midbody. MgcRacGAP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 46 publications
15
164
0
2
Order By: Relevance
“…Several GAP-defective Rho GAPs act in a dominant negative manner by sequestering substrate GTPases, preventing their inactivation but still allowing their interaction with downstream effectors (23,29,32). We showed that the GAP mutants of Abr and Bcr could still bind to caRac, providing evidence that these act as dominant negative proteins.…”
Section: Discussionmentioning
confidence: 66%
“…Several GAP-defective Rho GAPs act in a dominant negative manner by sequestering substrate GTPases, preventing their inactivation but still allowing their interaction with downstream effectors (23,29,32). We showed that the GAP mutants of Abr and Bcr could still bind to caRac, providing evidence that these act as dominant negative proteins.…”
Section: Discussionmentioning
confidence: 66%
“…RacGAP1 is a GTPase-activating protein that has been implicated in controlling cell growth and differentiation (35) and cytokinesis (25) (24,36), and this may depend on its phosphorylation status (37). In contrast, some studies suggest that RacGAP1 is able to mediate some of its functions independently of its GAP activity (38).…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemistry of hESC monolayers demonstrated that, as seen for other cell types (25,26), RacGAP1 localized to the nucleus and cytosolic structures of hESCs (Fig. 6B).…”
Section: Levels Of Hesc Racgap1 Are Decreased Locally In Response To Thementioning
confidence: 99%
“…Interestingly, both NLS sequences are strictly conserved among all vertebrate homologues of CHO1, identified in human, mouse, chicken and zebrafish . Moreover, all three proteins: CHO1/MKLP1, CYK-4/ MgcRacGAP, and Rho GEF ECT2, which appear to exist in a complex (Somers and Saint, 2003), have an NLS and are localized to the nucleus in mammalian cells (Tatsumoto et al, 1999;Hirose et al, 2001;Mishima et al, 2002), suggesting the importance of nuclear localization. Therefore, CHO1 may have to establish interactions with those molecules to become fully active during cytokinesis.…”
Section: Role Of the Nls-containing Regionmentioning
confidence: 99%